2021
DOI: 10.1101/2021.10.13.21264937
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparative effectiveness of ChAdOx1 versus BNT162b2 COVID-19 vaccines in Health and Social Care workers in England: a cohort study using OpenSAFELY

Abstract: Background: The UK COVID-19 vaccination programme delivered both the BNT162b2 mRNA (Pfizer-BioNTech) and the ChAdOx1 (Oxford-AstraZeneca) vaccines during overlapping periods, providing a rare opportunity to emulate a trial that directly compares both vaccines using routinely-collected NHS data. Frontline Health and Social Care workers comprise a useful population to assess comparative effectiveness due to early vaccine eligibility and relatively high post-vaccination transmission risk due to occupational expos… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…[1][2][3][4]21 A recent study examined the effectiveness of ChAdOx1 versus BNT162b2 COVID-19 vaccines in health and social care workers in England and found no difference in the risk of SARS-CoV-2 infection or COVID-19 disease up to 20 weeks after first dose of vaccination by vaccine type. 22 Our data support this finding up to 20 weeks, but suggest that from this point onwards the risk of breakthrough infection for BNT162b2 is approximately half of ChAdOx1, and our anti-S levels may give an indication of the underlying correlates for this increased risk.…”
Section: Discussionsupporting
confidence: 80%
“…[1][2][3][4]21 A recent study examined the effectiveness of ChAdOx1 versus BNT162b2 COVID-19 vaccines in health and social care workers in England and found no difference in the risk of SARS-CoV-2 infection or COVID-19 disease up to 20 weeks after first dose of vaccination by vaccine type. 22 Our data support this finding up to 20 weeks, but suggest that from this point onwards the risk of breakthrough infection for BNT162b2 is approximately half of ChAdOx1, and our anti-S levels may give an indication of the underlying correlates for this increased risk.…”
Section: Discussionsupporting
confidence: 80%
“…that have demonstrated little difference in initial protection from infection 14 or from severe disease and death 1,3 after ChAd/ChAd or BNT/BNT, despite BNT generating levels of neutralising antibodies many times higher than ChAd. 8 The importance of antibody-mediated immunity in protection against SARS-CoV-2 infection has been demonstrated in non-human primates and humans from both infection and immunisation, although correlates of protection against asymptomatic infection are not yet clear.…”
Section: Implications Of All the Available Evidencementioning
confidence: 99%
“…However, a recent preprint study by Hulme et al 14 showed no difference among recipients of these two vaccines regarding the risk of SARS-CoV-2 positive test, COVID-19 related accident & emergency attendance and hospital admission. Several fundamental factors might explain the disagreement with our results.…”
Section: Discussionmentioning
confidence: 97%